Triangulation of perspectives in physics classes - Kohler, Alaric; Perret-Clermont, Anne-Nelly (My University, 2016)
Among the challenges of a pedagogy engaging students into argumentative discussion Schwarz & Baker (2015) point out the fact that work on argumentation in science education often makes little use of the recent developments of theories of argumentation. In the present study, we would like to develop an approach of argumentation in science education by means of a theory (Grize's) that takes into account how students think in social interaction with the mediation of language and other signs. We will illustrate this with a case-study in a physics class in a Swiss high school, investigating the situated micro-history of meaning making in the perspective of each interlocutors. This contribution illustrates the potential of an argumentation theory as an instrumental resource to advance the psychology of learning, opening the way for an analysis of meaning making that is singular, situated and nevertheless accounts for some cognitive aspects of the activity.
, Joint SIG 20 and SIG 26 Meeting “Inquiry and Argumentation: Education for Thinking”, European Association for Research on Learning and Instruction (EARLI), University of Ghent, Ghent, Belgium
Keywords: perspectives situation of misunderstanding argumentation critical incident